PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA PENJARA DARIPADA REHABILITASI TERHADAP PENYALAHGUNA NARKOTIKA DI PENGADILAN NEGERI PEKANBARU KELAS IA - Fijai Sanjaya; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This thesis aims to find out the considerations of judges in imposing prisonsentences on narcotics abusers at the Pekanbaru District Court Class IA.Narcotics abuse is a serious problem that affects society at large. Judges asimportant decision makers in the criminal justice system play a role in decidingwhether narcotics abusers should be given prison sentences or given otheralternatives such as rehabilitation. This study aims to determine theconsiderations of judges in making decisions on imprisonment and the factors thatinfluence it at the Pekanbaru District Court Class IA. In Law Number 35 of 2009concerning Narcotics it is explained that Narcotics abusers must not be jailed butsentenced to Rehabilitation because the Narcotics Law guarantees abusers getrehabilitation efforts (Article 4d). In this writing, the writer focuses on NarcoticsAbuser, who in practice, the view of Narcotics Abusers as perpetrators of crime isstill more dominant than the health and healing approach to Narcoticsdependence. The purpose of writing this thesis: first, to find out what are theobstacles faced by Class IA Pekanbaru District Court Judges to ProvideRehabilitation for Narcotics Abusers. Second, to find out what the PekanbaruDistrict Court Judge considers in imposing prison criminal sanctions on narcoticsabusers. Third, to find out what are the efforts to overcome the obstacles toimplementing the rehabilitation of narcotics abusers. The research methodologyinvolves collecting primary data through interviews with judges who areauthorized to try cases of narcotics abuse at the Pekanbaru District Court ClassIA. In addition, secondary data consisting of court decisions and relevant lawsand regulations.From the research results, there are 3 main things that can be concluded:First, the consideration of the Class IA Pekanbaru District Court Judge isconsidering that because of all the elements of Article 112 paragraph (1) inconjunction with Article 132 paragraph (1) RI Law number 35 of 2009concerning Narcotics and secondly Article 127 paragraph (1) letter a RI Lawnumber 35 of 2009 in conjunction with article 55 paragraph (1) to 1 of theCriminal Code is fulfilled. Second, the obstacles in the implementation ofrehabilitation can be seen from the perspective of law enforcement officials, andthe existence of a double track system in the law itself. Third, efforts that can bemade in dealing with obstacles in the implementation of rehabilitation